Supplementary information and source code for "An atypical class of non-coding small RNAs produced in rice leaves upon bacterial infection" - Reshetnyak, Ganna; Jacobs, Jonathan M.; Auguy, Florence; Sciallano, Coline; Claude, Lisa; Medina, Clemence; Perez-Quintero, Alvaro J.; Comte, Aurore; Thomas, Emilie; Bogdanove, Adam; Koebnik, Ralf; Szurek, Boris; et al. (DataSuds, 2021)
This dataset contains additional supporting information and source code related to the discovery of Xanthomonas-induced small RNAs (xisRNAs) as described in the Related Publication. Deep small RNA (sRNA) sequencing analysis discovered a class of sRNA in rice (Oryza sativa) specifically associated with foliar diseases caused by Xanthomonas oryzae pathovars. A set of 163 xisRNAs loci were distinctively upregulated in response to various bacterial strains at an early stage of infection. Most xisRNA loci overlap with annotated cis-transcripts sequences often encoding protein kinase domain proteins including RLKs and RLCKs. A number of the corresponding rice cis-genes have documented functions in immune signaling and about one third of the xisRNA loci coincide with the coding sequence of a conserved kinase motif. xisRNAs exhibit features of small interfering RNAs and their biosynthesis depend on canonical components OsDCL1 and OsHEN1. Notably xisRNAs production was dependent on the X. oryzae Type III secretion system, a major bacterial virulence factor for host colonization. xisRNA induction possibly mediates post-transcriptional gene silencing but they do not appear to widely suppress cis-genes expression on the basis of mRNA-seq data. Overall, our results identify an unrecognized group of unusual sRNAs with a potential role in plant-microbe interactions. The main entry point for this dataset is the "PHIM_ xisRNA_MS_dataverse_code.html" file that records the code and the output of most secondary analysis computing tasks performed to generate the material relevant to the manuscript on xisRNAs referenced in the Related Publication metadata. Other Files include selected data files that have been used or produced in the course of the analysis workflow.